Tumbling motion of 1I/'Oumuamua and its implications for the body's distant past. (May 2018) - Drahus, Michał; Guzik, Piotr; Waniak, Wacław; Handzlik, Barbara; Kurowski, Sebastian; Xu, Siyi
Abstract Models of the Solar System's evolution show that almost all the primitive material leftover from the formation of the planets was ejected to the interstellar space as a result of dynamical instabilities1 . Accordingly, minor bodies should also be ejected from other planetary systems and should be abundant in the interstellar space2, giving hope for their direct detection and detailed characterization as they penetrate through the Solar System3, 4 . These expectations materialized on 19 October 2017ut with the Panoramic Survey Telescope and Rapid Response System's discovery of 1I/'Oumuamua5 . Here, we report homogeneous photometric observations of this body from Gemini North, which densely cover a total of 8.06 h over two nights. A combined ultra-deep image of 1I/'Oumuamua shows no signs of cometary activity, confirming the results from other, less sensitive searches6–9 . Our data also show an enormous range of rotational brightness variations of 2.6 ± 0.2 mag, larger than ever observed in the population of small Solar System objects, suggesting a very elongated shape of the body. Most significantly, the light curve does not repeat exactly from one rotation cycle to another and its double-peaked periodicity of 7.56 ± 0.01 h from our data is inconsistent with earlier determinations6, 7, 10–12 . These are clear signs of a tumbling motion, a remarkable characteristic of 1I/'Oumuamua's rotation that is consistent with a collision in the distant past. Bearing marks of a violent history, this first-known interstellar visitor tells us that collisional evolution of minor body populations in other planetary systems might be common. 1I/'Oumuamua observations from the Gemini North telescope, spanning approximately 8 hours on 27–28 October 2017, characterize the magnitude variations of the object and detect its tumbling nature, triggered by an old collision when it was still in its home system.